Reaction of [Os3(CO)10(NCMe)2] with isatin: Regiospecific μ-(N,O) coordination of theisatinate ligand to the triosmium framework (Journal of Bangladesh Academy of Sciences, 2026)
Treatment of activated [Os3(CO)10(NCMe)2] cluster with isatin (1H-indole- 2,3-dione) at room temperature furnished a new hydrido-bridged triosmium isatinate complex, [Os3(CO)10(μ-H)(μ-κ1(N)κ1(O)-C6H4(CO)2N)] (1) in a moderate yield. The compound is formed through the oxidative N–H bond activation, accompanied by regiospecific μ-(N,O) coordination to the Os3 framework. Characterization of 1 was done by elemental analysis, infra red, spectroscopy, 1H NMR spectroscopy, and X-ray diffraction analysis. The bonding in 1 has been investigated based on the density functional theory (DFT) method. The DFT-optimized geometry is similar to its solid state structure and the simulated structure parameters are in good agreement with the measured values.J. Bangladesh Acad. Sci. 50(2); 197–206: June 2026